Diretrizes Brasileiras de Dispositivos Cardíacos Eletrônicos Implantáveis (DCEI) - Parte IV - Cardíacas - Sobrac/SBC, Sociedade Brasileira de Arritmias (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
The latter part in these guidelines focuses on special recommendations in the artificial cardiac stimulation area, especially the circumstances the may interfere with the good relationship of pace-maker and guide-wire, heart and patient. The most important points mentioned here are associated with probable damages to guide-wires, especially in the infectious process, situations that often become dramatic in debilitated patients and that involves difficult decisions to be made such as the prolonged handling of the devices, controversial subject in the literature. The other important and often discussed fact in this chapter is related to the environmental interferences which may inhibit or disturb the previous programming thus leading to unevenness between the pacemaker and the heart. It becomes more and more frequent due to the technological evolution impact among the electro-electronic equipments that surround a patient with pacing.